2017
DOI: 10.1002/bdd.2077
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic analysis of inhaled salmeterol in asthma patients: Evidence from two dry powder inhalers

Abstract: Salmeterol (SAL) is a long-acting β2-adrenergic agonist, which is widely used in the therapy of asthma. The aim of this study was to investigate the pharmacokinetics (PK) of inhaled salmeterol in asthma patients using two different dry powder inhalers. This analysis was based on data from 45 subjects who participated in a two-sequence, four-period crossover bioequivalence (BE) study after single administration of the test (T) and reference (R) products. In order to mimic more closely the real treatment conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
(85 reference statements)
1
3
0
Order By: Relevance
“…The available plasma PK data allowed the estimation of systemic PK parameters for FP, LIN, and IND. The plasma PK of SAL, FP, and LIN were best described by two-compartment models, which is in accordance with the literature [9,21,22]. While LIN PK in rats was previously only described by non-compartmental analysis [23], compartmental analyses of human PK typically do employ two compartments [24][25][26], which supports the use of a two-compartment PK model.…”
Section: Discussionsupporting
confidence: 81%
“…The available plasma PK data allowed the estimation of systemic PK parameters for FP, LIN, and IND. The plasma PK of SAL, FP, and LIN were best described by two-compartment models, which is in accordance with the literature [9,21,22]. While LIN PK in rats was previously only described by non-compartmental analysis [23], compartmental analyses of human PK typically do employ two compartments [24][25][26], which supports the use of a two-compartment PK model.…”
Section: Discussionsupporting
confidence: 81%
“…This ethanolamine group in SMT is present in all the β2-AR agonists and antagonists that were identified as VMAT2 stabilizers and is most likely an important contributor to the binding of these compounds to VMAT2. Although inhaled β2-AR agonists such as SMT and formoterol act locally in the lung, there is also systemic absorption across the pulmonary vascular bed and from the gastrointestinal tract due to the high gut deposition of inhaled drugs 53 , 54 . SMT and formoterol can also partially cross the BBB 55 , 56 and can thus potentially affect VMAT1 or VMAT2 function both in the CNS and outside the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Noncompartmental analysis (NCA) showed that t max of HS‐25 varied greatly among subjects, from 0.5 to 12 hours after dosing, and the maximum plasma concentration (C max ) and areas under curve (AUC) did not present good linearity with dose 3 . Unlike NCA, a model‐based approach allows for a better approximation of drugs' pharmacokinetics (PK) and enables a further characterization of the PK process such as absorption, distribution and metabolism 5 . Population PK (PopPK) modelling, which quantitatively estimates the PK characters of drugs, as well as the PK variability in the population of interest, is a useful tool for new drug development.…”
Section: Introductionmentioning
confidence: 99%
“…3 Unlike NCA, a model-based approach allows for a better approximation of drugs' pharmacokinetics (PK) and enables a further characterization of the PK process such as absorption, distribution and metabolism. 5 Male and female healthy subjects aged 18-45 years with body mass index 19-28 kg/m 2 were eligible for the study. Subjects were required to be nonsmokers with no history of alcohol or drug abuse.…”
mentioning
confidence: 99%